Artificial sensory techniques for halal authentication - Ismarti, Soheib; Triyana, Kuwat; Ahmad Fadzillah, Nurrulhidayah; Nordin, Noor Faizul Hadry (Global Science, 2020)
Halal industry and services being a global issue nowadays. Not only for Muslim majority countries but also for the countries where the Muslim as the minority, since there is a great potency business behind the term ‘halal’. Halal industry has been growth in all sectors and is a trend as a lifestyle. With the increasing in halal awareness, the demand for halal products and services also increase significantly. One of the critical aspects in halal assurance system is traceability and authentication. Authentication of food is important for the food processor, retailers, consumers, and also regulatory authorities due to adulteration and fraudulent practices in the industry sector. Various methods and authentication techniques have been developed to protect consumers and screen for the adulteration in the food chain; however, many methods for halal authentication were used high-end technology, required high-skill, time consuming, and costly. Thus, research needs to encourage the development of the simple instrument with high accuracy, sensitivity and selectivity to support halal industry. This paper focuses on artificial sensory techniques (electronic nose and electronic tongue) within the frame of halal authentication on food and beverages. The characteristics and application of these equipment along with the challenges and perspective are discussed.